COLLABORATIVE LEARNING IN ISLAMIC RELIGIOUS EDUCATION: AN EFFORT TO BUILD TOLERANCE AMONG STUDENTS AT SMA SENOPATI SEDATI SIDOARJO - Cornelya Hadi, Imaudy; Tamin AR, Zaini; Darmawan, Agus (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2025)
Abstract: Amid the growing diversity of cultural, ethnic, and religious backgrounds in Indonesia, fostering a spirit of tolerance among students has become a critical challenge in today’s educational landscape. This study stems from concerns over the predominantly one-way instructional approach in Islamic Religious Education, which often lacks space for inclusive dialogue among students. The research aims to explore how the implementation of collaborative learning methods in Islamic Religious Education can contribute to cultivating tolerance among students at SMA Senopati Sedati Sidoarjo. Employing a qualitative approach and case study design, data were collected through classroom observations, in-depth interviews with Islamic Religious Education and Christian Religious Education teachers, and analysis of instructional documents. The findings indicate that collaborative strategies—such as diverse group work, cross-perspective discussions, and joint projects rooted in moderate Islamic values—can foster a more open and respectful learning environment. Students became more engaged in discussions and accustomed to listening to differing viewpoints without judgment. Nevertheless, challenges such as uneven learning motivation and limited resources remain obstacles. These findings suggest that participatory and contextual Islamic Religious Education instruction is not only relevant but also effective in shaping a more tolerant younger generation, better prepared to thrive in a pluralistic society. Keywords: Collaborative Learning Islamic Religious Education, , Religious Moderation, Tolerance.